Implementation of the Professional Nursing Practice Model at Hospitals in Kotamobagu - Heriyana Amir; Suci Rahayu Ningsih (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2022)
Success in providing nursing is directly proportional to the success of the nursing management process, because to create high-quality services, professional services are needed which are technically to improve each system of providing nursing care, for that the provision of nursing through the Professional Nursing Practice Model (MPKP) is considered very important. The results of the survey conducted by researchers obtained information related to the professionalism of nurses by 5 informants, that the nursing services they felt were still unsatisfactory. The purpose of this study was to determine the Professional Nursing Practice Model (MPKP) before and after being given treatment. This research is a type of quantitative research with a pre-experimental one group pre-test post-test design. The population in this study were all nurses who were permanent employees at hospitals in Kotamobagu City with a total of 257 people. The total sample of this study was 154 people who were determined based on the Slovin formula. The sampling technique used is the probability sampling method by accidental proportion based on the hospital cluster. The results of this study indicate that the frequency distribution of Pillar I of the management approach at Kotamobagu City Hospital has increased after being given the application of MPKP to each element and the frequency distribution of Pillar IV of the nursing care delivery system at Kotamobagu City Hospital has increased in each element after being given professional training.